Case study strategies for architects and designers : integrative data research methods - Sarvimaki, Marja (London, United Kingdom : Taylor & Francis, 2018)
Case Study Strategies for Architects and Designers explains methods in evidence-based design, also called practice-based research, to show you the value of research to your designs. Topics covered pertain to data collection and analysis techniques, including surveys, interviews, fieldwork, participatory design, occupancy evaluations, and memory sketching. Integrative data evaluation, theoretical sampling, triangulation, pattern matching logic, and analytical generalization are also discussed. Global research precedents, exercises, further reading, section summaries, sidebars, more than 30 black and white images and tables will help you conduct empirical inquiries in real-life contexts.
Chapter 1. The Interdisciplinary realm -- Chapter 2. Quantitative vs. Qualitative strategies -- Chapter 3. Integrative data evaluation -- Chapter 4. Epilogue -- List of Figures.
Includes bibliographical references and index.
Keywords: ARCHITECTURE PROFESSIONAL PRACTICE